CGMP–cAMP interplay in cardiac myocytes: a local affair with far-reaching consequences for heart function. (19th January 2012) - Stangherlin, Alessandra; Zaccolo, Manuela
Abstract : cAMP and cGMP signalling pathways are common targets in the pharmacological treatment of heart failure, and often drugs that modulate the level of these second messengers are simultaneously administered to patients. cGMP can potentially affect cAMP levels by modulating the activity of PDEs (phosphodiesterases), the enzymes that degrade cyclic nucleotides. This biochemical cross-talk provides the means for drugs that increase cGMP to concomitantly affect cAMP signals. Recent studies using FRET (fluorescence resonance energy transfer) reporters and real-time imaging show that, in cardiac myocytes, the interplay between cGMP and cAMP has different outcomes depending on the specific location where the cross-modulation occurs. cGMP can either increase or decrease the cAMP response to catecholamines, based on the cyclase that generates it and on the PDEs associated with each subcellular compartment. cGMP-mediated modulation of cAMP signals has functional relevance as it affects protein phosphorylation downstream of protein kinase A and myocyte contractility. The physical separation of positive and negative modulation of cAMP levels by cGMP offers the previously unrecognized possibility to selectively modulate local cAMP signals to improve the efficacy of therapy.